Genetic diversity and runs of homozygosity analysis of Hetian sheep populations revealed by Illumina Ovine SNP50K BeadChip - Han, Zhipeng; Zhou, Wen; Zhang, Lulu; Wang, Ruotong; Liu, Chunjie; Bai, Xinyu; Liu, Shudong (Frontiers in Ecology and Evolution, 2023)
Hetian sheep have a long history and a wide distribution. They are renowned for their carpet-grade wool, which makes them a valuable genetic resource in China. The survey revealed that Hetian sheep primarily inhabit three distinct ecological environments: Mountains (MTS), Mountain-Grasslands (MGTS) and Grasslands (GTS). To understand the evolutionary relationships and germplasm characteristics of Hetian sheep in these diverse environments, we randomly selected 84 healthy adult ewes from each of these ecological regions. We obtained the Illumina Ovine SNP50K BeadChip by extracting DNA from Hetian sheep ear tissue using the phenol-chloroform method. Afterward, we conducted a population genetic structure and genetic diversity analysis of Hetian sheep using the Illumina Ovine SNP50K Beadchip. Principal Component Analysis (PCA) and Neighbor-Joining (NJ) phylogenetic analysis indicated that Hetian sheep in three different ecological environments exhibit distinct genetic distances. Admixture analysis indicated that MGTS and GTS share a common ancestral origins. Additionally, the Linkage disequilibrium (LD) analysis indicated that M had the highest decay rate, while MG had the lowest decay rate. Furthermore, we identified the overlapping homozygous genomic regions of Hetian sheep in the three ecological environments through runs of homozygosity (ROH) analysis. We subsequently performed gene annotation and enrichment analysis on these overlapping genomic regions. In the MTS environment, we identified 31 candidate genes associated with high-altitude environmental adaptation. These genes are involved in bone cell generation, differentiation, and the maintenance of bone homeostasis (WNT6, WNT10A, CHSY1), tooth and tongue development (LEF1, TP63, PRDM16), as well as hearing and visual functions (RBP4, ATF6, JAG1). In the GTS environment, we identified 22 candidate genes related to economic traits, including those associated with reproduction (PLA2G4F, ACVR1, ADCY2) and growth (CAPN3, YAP1, FGF9). Research indicates that Hetian sheep can be divided at the genomic level into three subtypes: MTS, MGTS, and GTS. This enhances the genetic diversity of Hetian sheep germplasm resources and provides guidance for the conservation of Hetian sheep breeds. Additionally, we have identified genes related to multiparous traits in MGTS and GTS, offering insights for the selection and breeding of multiparous Hetian sheep.